University Students' Perception and Use of ChatGPT: Generative Artificial Intelligence (AI) in Higher Education - Obenza, Brandon Nacua; Salvahan, Alexa; Rios, Alexandra Nicole; Solo, Althea; Alburo, Rea Ashlee; Gabila, Rey Jose (Research Parks Publishers, 2024)
This quantitative study examined how university students perceive and use generative AI technology, specifically ChatGPT, in higher education. The main objective is to explore and describe university students' perception and use of generative AI, particularly ChatGPT, in the context of higher education. A 5-point Likert scale questionnaire was adopted and used in the study. Five hundred students from various universities in Region XI were surveyed using a stratified random sampling technique. Further, the validity and reliability of the scale used in the study were assessed using Cronbach's Alpha and Factor Analysis and demonstrated acceptable construct validity and reliability indices. The findings revealed that university students demonstrated high levels of understanding, knowledge, perception of the advantages and disadvantages, positive attitude, and strong intention to use generative AI technologies in the context of higher education. Moreover, the respondents showed a moderate level of concern about generative AI.